Jonas Šulcas, Translator of Aesop’s Fables: Traces of His Biography - Triškaitė, Birutė (Senoji Lietuvos literatūra, 2024)
The focus of this article is Johann Schultz (Lith. Jonas Šulcas, 1678–1709), a participant in the philological dispute that arose in Prussian Lithuania at the beginning of the eighteenth century, who is best known in the history of Lithuanian literature for his translation of the first Lithuanian book of fiction, Ezopo pasakėčios (Aesop’s Fables; Königsberg, 1706) and as a folklore collector. In contrast to the main opponents in this debate – the long-standing Prussian Lithuanian clergymen, the priest of Gumbinė (Ger. Gumbinnen) Michael Mörlin (Lith. Mykolas Merlinas, 1641–1708) and the then priest of Valtarkiemis (Ger. Walterkehmen) Jacob Perkuhn (Lith. Jokūbas Perkūnas, 1665–1711) – biographical information on Johann Schultz, who was perhaps the youngest participant in this linguistic dispute, has been scarce so far. Based on documents in the Secret State Archives Prussian Cultural Heritage Foundation (Ger. Geheimes Staatsarchiv Preußischer Kulturbesitz) in Berlin and Johann Jacob Quandt’s (Lith. Jonas Jokūbas Kvantas, 1686–1772) manuscript Preußische Presbyterologie (5 vols, before 1772), the article reconstructs the hitherto unknown facts of Johann Schultz’s biography and corrects the previously unsubstantiated claims in the historiography of Lithuanian literature. The study conducted leads to the following main conclusions: 1. According to Johann Schultz’s matriculation record in the registers of the University of Königsberg, which shows that he did not start his studies on 18 June 1704 as hitherto believed, but much earlier, on 9 May 1695, and that he took the academic oath at the time of his enrolment, it is likely that Schultz was born in about 1678 (and not in 1684, as assumed so far). 2. Archival documents reveal that Johann Schultz’s father was Michael Schultz (1632–1710), a priest of Katniava (Ger. Kattenau). He came from Tilžė (Ger. Tilsit) and served for several decades in Katniava, first as a precentor and from 1675 until his death as a priest. Johann Schultz’s mother is believed to have been Dorothea Cellin (1647–?), the granddaughter of Barthel Horn, the presumed founder of the Horn scholarship (Lat. Stipendium Hornianum). 3. Before his studies at the University of Königsberg, Johann Schultz graduated successfully from the Tilžė provincial school (also known as the Tilžė Latin or particular school) as evidenced by the reference of Heinrich Tilesius (1666–1732), the then rector of the school. 4. Archival sources show that while studying at the University of Königsberg, Johann Schultz was a student of two famous theology professors, Friedrich Deutsch (1657–1709) and Bernhard von Sanden Jr (1666–1721). While still a student, at least from 1696 onwards, Johann Schultz had a preaching apprenticeship with Prussian Lithuanian priests. One of them was Michael Mörlin, the priest of Gumbinė, the initiator of the linguistic polemic of the early eighteenth century. Later Schultz not only supported Mörlin’s linguistic ideas but also tried to realise them in his translation of Aesop’s fables. They came to know each other even before the beginning of the dispute. 5. Recently found primary sources necessitate the correction of the claim about the date and place of Johann Schultz’s death – that he was a priest in Tilžė where he died in 1710 – which has been repeated over and over again in the historiography of Lithuanian writing. Johann Jacob Quandt’s manuscript presbyterology and other archival documents leave no doubt: the translator of Aesop’s fables died on 30 December 1709 in Lazdynai (Ger. Lasdehnen) and not in 1710 in Tilžė as has been claimed until now. Like his father Michael, Johann Schultz was one of the many priests in Prussian Lithuania whose lives were claimed by the Great Plague. According to Quandt, Schultz was laid to rest in the churchyard of Lazdynai church.